KARAKTERISASI ISOLAT LOKAL Bacillus sp. POTENSIAL SEBAGAI BIOLARVASIDA HASIL ISOLASI DARI LARVA NYAMUK DAN ENDAPAN TEMPAT PERINDUKAN NYAMUK Aedes aegypti - Mufida Utami Rizka (PT Innovative Academic Journals, 2025)
Application of chemical insecticides as a DHF vector control has some negative impact so it needs to be handled by aplication of bioinsectisides from potential bacterias one of which is bacterias from genus Bacillus. This research aims to find out the characteristics of potential Bacillus that isolation from mosquito larvae and sediment breeding places of Aedes aegypti which has been potential tested and has the highest mortality to Aedes aegypti larvae, so the species of Bacillus that can be used to bionsectisides can be known. Characterization in this research involved macroscopic characterization, microscopic characterization, and physiological characterization from each isolate from the results of isolation in Aedes aegypti larvae and sediment breeding places of Aedes aegypti, which is then the percentage of similarities index with comparable coefficient calculated between isolate of bacillus were isolated and species of bacillus in the reference book Bergey’s Manual of Systematic Bacteriology 2nd edition, so the species name of Bacillus was obtained. Isolate EG6(4), ES7(3), and LS9(1) is Bacillus thuringiensis with each similarity percentage 80,6%, 78,12%, and 62,5%, while isolate ES4(3), LSDA4(2), and LS3(3) is Bacillus sphaericus with each similarity percentage 71,4%, 82,6%, and 63,3%. In this case, molecular characterization is still needed to ensure more about the species name of each isolates.